KOMUNIKASI INDONESIA (Studi Komunikasi Nusantara Perspektif Integrasi Interkoneksi) - Mokhamad Mahfud (Profetik: Jurnal Komunikasi, 2013)
The term “think globally and act locally” has begun to surface since the eighties, but until now, a quarter centurylater, there was also a surefire formula go see about it. Human experience feel things that otherwise like SARA (suku, agama dan ras) events that befall the nation, instead of peace, mutual trust, peaceful coexistence, at-ta’ayus as-silmi, tolerance, tasamuh among fellow human beings and between groups, but rather violence, violence , prejudice (prejudice), azsu’uzan religion, ethnicity, class, race, interests, both at the local, regional, national and even international (global). As if all want to reverse the adage “think locally and act only”, without having coupled “think globally”. In the associate, connect and communicate with other groups and do not feel the need to consider the governance rules, laws, agreements and international relations.Each ethnic group, religion, class, culture wants to maintain, even cult, sect or school of thought wanted to strengthen and reinforce certain local religious identity, cultural identity, ethnic identity, political identity as felt in the shadow of the threat of domination and cultural hegemony, certain foreign cultures or civilizations. Pressure of social psychology in the real and the imagined then cause unfair treatment (injustice), discriminatory (political behavior discrimination of race, ethnicity, religion and origin) and subordinate (humble and do not consider important the presence of another person or group), here as if there is no problem indeed, in maintaining the identity and group identity, but the ripples that appear in events locally, regionally, nationally and internationally to prove there is indeed a problem in the social order of the world.This paper offers a model of communication between fellow men’s race (human), which integrates and connectedness with nature and God (spirituality), in the context of Communication Studies allows develop integrationinterconnection study Communications, for example, the model rialektika between Islamic, and Indonesian-ness can Modernity in trialektika developed to initiate some sort of communication.